Treatment of CMV Retinitis with Intravitreal Ganciclovir in the HAART Era. (1st October 2001) - Campbell, Robert J; Chow, Benjamin; Victor, Gary; Kravcik, Steven; Hodge, William G
Abstract : OBJECTIVE: To describe the course and outcome of cytomegalovirus (CMV) retinitis among AIDS patients treated with intravitreal ganciclovir and systemic highly active antiretroviral therapy (HAART). The secondary objective was to compare the course of CMV retinitis between patients receiving HAART and those not receiving this treatment. DESIGN: A retrospective cohort design consisting of 21 eyes from 16 patients with AIDS and CMV retinitis consecutively enrolled between January 1996 and August 1999. All patients received intravitreal ganciclovir therapy, and half of the patients began HAART as well. Duration of intravitreal therapy and ensuing disease quiescence, as well as CD4+ T cell counts at diagnosis and at cessation of ganciclovir, were calculated. Secondly, instantaneous hazards for outcomes such as CMV retinitis progression, ocular complications and mortality were compared. SETTING: Tertiary care centre in Ottawa, Ontario. RESULTS: Five of eight patients receiving HAART discontinued intravitreal ganciclovir after a mean treatment period of 428 days. During this period, their mean CD4+ count rose from 7.5 to 190/mL. Subsequently, none of these patients experienced retinitis progression during follow-up periods lasting up to 820 days (mean of 617 days). Progression of CMV retinitis was 11.4 times more likely among those not receiving HAART (P=0.049). CONCLUSIONS: On initiating HAART, patients with CMV retinitis may enjoy significant recovery in CD4+ counts and sustained retinitis quiescence without specific anti-CMV therapy. Intravitreal ganciclovir injections seem well suited to offer effective CMV control during temporary periods of decreased CD4+ counts while awaiting HAART-mediated immune system reconstitution.